Online Complaints on Hotel Services in Indonesia: A Comparison Study of Asian and English-Speaking Country Visitors - Nurhikmawati, Agita Risma; Puspitasari, Dhika (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
Communication in the Indonesian hospitality industry impacts on the growth of domestic and foreign tourists’ number who visit the country. And one of the communication forms in this business is visitor review on hospitality platforms. This review offers several advantages since, for example, hotels will be able to find out customers' levels of satisfaction, needs, or complaints on hotel services and facilities. And these aspects can be used to evaluate the business’ performance in gaining profit. Based on that urgency, this study aims to investigate the complaint structures and strategies written by Asian and English-speaking country visitors on both domestic chain hotels (DCH) and international chain hotels (ICH) in the TripAdvisor page, an international-based travel site. Furthermore, a qualitative descriptive research method is employed along with note-taking as the data collection technique, and the theory used is the complaint speech act strategy presented by Trosborg. The results of this study indicate that the complaint structure consists of several components, namely: title, opening sentence, content (complaint sentence), closing sentence, and parting or valediction. In detail, the structure component that appears the least is parting since it is only found in Asian visitor reviews on ICH. While, the most common complaint strategy used by DCH and ICH visitors is annoyance. It can be concluded that there is no significant difference in the use of complaints strategies between Asian and English-speaking country visitors in both DCH and ICH. It happens due to globalization where the world communities carry out high mobility between cultures even though they have geographical boundaries; thus, they are able to influence each other frequently